A reevaluation of the specimens of Mesocoelium (Trematoda: Mesocoeliidae) in the Colección Nacional de Helmintos, Mexico - López-García, Ashley Samara; García-Prieto, Luis (Zootaxa, 2017)
Species of Mesocoelium Odhner, 1901 (Digenea) are generally similar and are often difficult to distinguish. Currently there are 42 specimens of this genus held in the Colección Nacional de Helmintos (CNHE) of the Instituto de Biología, Universidad Nacional Autónoma de Mexico, which previously have been assigned to three species: M. monas Rudolphi, 1819, M. travassosi Pereira & Cuocolo, 1940 and M. leiperi Bhalerao, 1936. Upon reevaluation of these specimens it was determined that 27, could not be assigned to species level and 15 could only be assigned to body type (carli and leiperi) because of the poor conditions of preservation of the material. The remaining 15 specimens were of sufficient quality to be identified to species and were found to represent M. americanum Harwood, 1932, M. danforthi Hoffman, 1935, M. meggitti Bhalerao, 1927, M. cf. americanum Harwood, 1932, and M. cf. danforthi Hoffman, 1935. Neither M. monas nor M. travassosi could be confirmed among these specimens; however, Mesocoelium meggitti (syn. M. travassosi) was confirmed. Mesocoelium danforthi is recorded for the first time in the Mexican collection. The presence of M. cf. gonocephali Singh, 1967 and M. cf. microon Nicoll, 1914 also among the 15 specimens of sufficient quality to be identified to species, needs to be confirmed through collects of new material. Finally, in future studies, we propose to improve the quality of specimens by fixing them considering the modifications to this process proposed herein, and compliment these morphological studies with molecular studies.